'Leaving No Child Behind': investigation on gross motor skill among autistic children - Man, Norkamariah; Ragbir Singh, Tarveen Kaur; Zainuddin, Zainal Abidin; Mohd. Hashim, Asha Hasnimy; Ibrahim, Halijah (2006)
Autism is defined as a developmental disability that affects the ability of a person to communicate, understand language, play, and interact with others (Dunlap & Bunton-Pierce, 1999). Children who suffer from autism usually show uneven gross and fine motor skills and lack of cooperativeness in group play. Opportunities should be given among autistic children to interact successfully with peers. An investigation was conducted to investigate the performance of gross motor skill among autistic children. Seven autistic children performed 20 items of Texas Revision of Fait’s Basic Motor Skills: Basic Movement Performance Profile (Faith, 1978). Results indicated that the autistic children scored lower than their normal peers. The mean score of gross motor activities indicated that autistic boys perform better than autistic girls. The autistic children showed difficulties in performing non-locomotors movements as compared to locomotors movements. Suitable physical activity program should be developed to widen the opportunity and increase physical ability of autistic children to interact and play with their peers.